An Index of Gender-Typed Portrayals in Preschool Television - Walsh, Abigail S. (Advances in Social Sciences Research Journal, 2021)
Little research has examined the gender representations in preschool television shows. Preschool-aged children use information in the world around them, including the television they watch, to inform gender-appropriate behaviors. This study analyzed gender-stereotyping in individual preschool television shows, by utilizing a cluster analysis to assess how characters were being portrayed in each show. From this analysis an index of gender-stereotyped representations in preschool television was created with shows ranging from stereotypical to counter-stereotypical. Results showed nuance in the types of stereotypical and counter-stereotypical representations in individual shows. Findings may inform parents’ television choices for their children, as well as content creators’ choices for future preschool television content.